2020
DOI: 10.1007/s12070-020-02153-9
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Foreign Body Displacement into the Maxillary Sinus as a Complication of Maxillofacial Interventions: Systematic Review

Abstract: Displacement of foreign bodies into the maxillary sinus shows an increasing tendency, especially in regard to raising amount of dental implant installation procedures. The purpose of our study was to compare the efficiency and the rate of late complications among the methods of removal of foreign bodies from maxillary sinus. We performed a systematic review following PRISMA Checklist, searching Pubmed and Google Scholar databases for studies investigating the methods of removal of foreign bodies from maxillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition to sinusitis, other sequelae such as mucous cyst, FB granuloma and, in more severe cases, pneumonia or lung abscess due to pneumatic aspiration, reasons why preventive FB removal is widely recommended [9]. Standardized management methods for removing objects displaced to MS are scarce in the literature, which makes it difficult to assess the effectiveness of different therapeutic approaches [10]. Factors such as FB size and location influence the appropriate choice [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to sinusitis, other sequelae such as mucous cyst, FB granuloma and, in more severe cases, pneumonia or lung abscess due to pneumatic aspiration, reasons why preventive FB removal is widely recommended [9]. Standardized management methods for removing objects displaced to MS are scarce in the literature, which makes it difficult to assess the effectiveness of different therapeutic approaches [10]. Factors such as FB size and location influence the appropriate choice [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that functional endoscopic sinus surgery be considered the gold standard for the treatment of FB in MS [8]. However, the inability of most dental professionals to perform this procedure [10] and the need for ample visualization of the cavity are disadvantages of this technique [12]. These aspects are not observed when Caldwell-Luc surgical access technique is employed, which offers ample space for the removal of FBs of different sizes and positions [12], which is why this technique was used in this report.…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic foreign body migration into maxillary sinus remains relatively rare complication, though exact morbidity seems to be underestimated and still rising. 10…”
Section: Discussionmentioning
confidence: 99%
“…Among the different methods, there are two treatment modalities proposed both to remove the foreign body and to treat the associated complications (if these exists): the transnasal approach with functional endoscopic sinus surgery (FESS) and an intraoral approach, through the anterior maxillary wall. In selected cases, these two modalities can be combined [3][4][5] . The purpose of this paper is to raise awareness upon the increasing incidence of the maxillary sinus foreign bodies with endodontic origin by summarising the diagnosing and treatment methods and presenting some cases of foreign bodies displaced into the maxillary sinus, surgically treated in our Department.…”
Section: Introductionmentioning
confidence: 99%